2013
DOI: 10.5935/abc.20130128
|View full text |Cite
|
Sign up to set email alerts
|

VEGF 165 Gene Therapy for Patients with Refractory Angina: Mobilization of Endothelial Progenitor Cells

Abstract: BackgroundVascular endothelial growth factor (VEGF) induces mobilization of endothelial progenitor cells (EPCs) with the capacity for proliferation and differentiation into mature endothelial cells, thus contributing to the angiogenic process. ObjectiveWe sought to assess the behavior of EPCs in patients with ischemic heart disease and refractory angina who received an intramyocardial injections of 2000 µg of VEGF 165 as the sole therapy. MethodsThe study was a subanalysis of a clinical trial. Patients with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…We observed that IV administration of BM-MSC and AD-MSC increased VEGF levels in lung tissue, which was not observed with the IT route. Based on previous studies of cardiac revascularization [ 50 , 51 ], we hypothesize that the systemic injection of BM-MSCs and AD-MSCs results in direct contact with the remaining endothelial cells of the pulmonary vasculature, stimulating them to synthesize VEGF. Intense neutrophilia in the sputum of COPD patients correlates positively with disease severity and high production of IL-8 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that IV administration of BM-MSC and AD-MSC increased VEGF levels in lung tissue, which was not observed with the IT route. Based on previous studies of cardiac revascularization [ 50 , 51 ], we hypothesize that the systemic injection of BM-MSCs and AD-MSCs results in direct contact with the remaining endothelial cells of the pulmonary vasculature, stimulating them to synthesize VEGF. Intense neutrophilia in the sputum of COPD patients correlates positively with disease severity and high production of IL-8 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is a highly-regulated process that is important in tissue repair, regeneration and embryonic development, with EPCs serving a central role in these functions (13). Previous studies have demonstrated that EPCs exhibit characteristics of directional differentiation into endothelial cells by homing in an ischemic region (14). EPCs not only participate in angiogenesis during embryonic development, but can also be differentiated into endothelial cells following birth (15).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that EPCs are the most advantageous source of seed cells for vascular repair due to their ability maintain vascular endothelial function and integrity (Landmesser et al, 2004). EPCs are recruited by cytokines and inflammatory factors to the intimal lining of the injured region and stimulate migration and proliferation of the neighboring endothelial cells by secreting angiogenic growth factors (Rodrigues et al, 2013). EPCs play a key role in the treatment of vascular stenosis; however, endogenous EPCs are limited in number and are insufficient to meet the need of clinical applications.…”
Section: Discussionmentioning
confidence: 99%